PENGARUH TERPAAN MOBILE ADVERTISING BERUPA SMS (SHORT MESSAGE SERVICE) OPERATOR KARTU AS TERHADAP SIKAP PENGGUNA TELEPON SELULER DI LINGKUNGAN MAHASISWA UNIVERSITAS RIAU - Noviri Syahdi; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research starts on the theory of S-O-R (Stimulus- Organism- Response) and the theory of three components of attitude, the theory of S-O-R assume that certain stimullus will produce a certain behavior anyway. The basic assumption of this theory is that communication is a process of action and reaction. In this research, see how cell phone users respond to mobile advertising expossure in the form of SMS promo by card operator As coming into his cell phone. SMS messages received promo operator with frequency so intense every day trigger a reaction by the attitude shown mobile phone users in the Riau University students. The purpose of this research is to determine, whether there is an influence of mobile advertising expossure in the form of SMS promo card operator As to the attitude of mobile phone users in the Riau University students.The method used in this study is a quantitative method of explanation. Data collection techniques in this study using a questionnaire. The number of samples for this study were 135 respondents. Sampling using unknowing populations and accidental sampling techniques. To determine how much influence these two variables, the researchers used a simple linear regression analysis. Questionnaire for data processing, carried out using the program Statistics Product And Service Solutions (SPSS) version of Windows 17.Results of research on the influence of mobile advertising expossure in the form of SMS promo card operator As to the attitude of mobile phone users in the Riau University students regression coefficient values obtained in this study is Y = Y = 5,377 + 1,144 X with significance level 0,000 that smaller than α = 0.05. This means that there is the influence of mobile advertising expossure in the form of SMS promo card operator As to the attitude of mobile phone users in the Riau University students of 55,1% and in the category of influential medium. These percentages indicate that there is a reaction to the stance taken or indicated respondents. Thus H0 is rejected and Ha accepted.Keywords: Mobile Advertising Expossure, SMS Promo, Attitude of Mobile Phone Users, Riau University Students.